Honey Creek: Sunday at the Sunflower Inn - Book 4 - Thomas, Jodi (New York, New York : Zebra Books/Kensington Publishing Corp., 2022)
"Jessica Ann McKenzie--"Jam" to everyone in Honey Creek-- has fulfilled her dream of owning the best restaurant for miles around. Serving candlelit dinners to every couple in town on Valentines Day is a reminder of another dream, one shes just about given up on. Until, that very night, Sergeant Tucson Smith clambers out of the muddy river and onto her land, bringing the promise of something theyve both been searching for. When McCoy Mason crashes on Interstate 45, he doesnt just bust up his Mustang, his leg, and his relationship. He also loses his prospects of a job and apartment in Houston. Honey Creek, home to his estranged grandfather, offers a temporary respite, a place to recover before moving on again. After all, what permanent use could a town so picture-perfect have for a man like him?"--
Keywords: Restaurateurs -- Fiction; Man-woman relationships -- Fiction; Interpersonal relations -- Fiction; City and town life -- Texas; Fiction; Texas -- Fiction; Romance fiction